Make: Arduino Bots and Gadgets - Karvinen, Tero (O'Reilly Media, 2012)
With Arduino, building your own embedded gadgets is easy, even for beginners. Embedded systems are everywhere--inside cars, children's toys, and mobile phones. This book will teach you the basics of embedded systems and help you build your first gadget in just a few days. Each learn-as-you-build project that follows will add to your knowledge and skills. Experiment with Arduino, the popular microcontroller board Build robots and electronic projects with easy-to-follow instructions Turn your ideas into working physical prototypes Use Android phones as remote controls in your projects Work with an uncomplicated programming language created for artists, designers, and hobbyists Get everyone involved, with projects that even beginners can build.